Financial Intermediation, Asset Prices, and Macroeconomic Dynamics - Emanuel Moench; Tobias Adrian; Hyun Song Shin (Verein für Socialpolitik, 2010)
Fluctuations in the aggregate balance sheets of financial intermediaries provide a window on the joint determination of asset prices and macroeconomic aggregates. We document that financial intermediary balance sheets contain strong predictive power for future excess returns on a broad set of equity, corporate, and Treasury bond portfolios. We also show that the same intermediary variables that predict excess returns forecast real economic activity and various measures of inflation. Our findings point to the importance of financing frictions in macroeconomic dynamics, and provide quantitative guidance for preemptive macroprudential and monetary policies.
Keywords: G10; G20; E32; 330; Return Predictability; Financial Intermediation; Macroeconomic Dynamics; Macroprudential Policy